SYNTHESIS AND SPECTRAL INVESTIGATION OF ANIONIC TETRAKIS-COMPLEXES OF RARE EARTH ELEMENTS WITH DIMETHYL-N-TRICHLORACETYLAMIDOPHOSPHATE AND TETRAPHENYLPHOSPHONIUM CATION: UDC 546.65+535.37 (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2018)
As a continuation of studies of carbacylamidophosphate based coordination compounds a series of the lanthanide and yttrium complexes of general formula PPh4[LnL4], where Ln = La, Nd, Tb and Y; L- = [CCl3(CO)N(PO)(OCH3)2]- has been synthesized. The resulting compounds were characterized by means of thermal gravimetric analysis, IR, 1H NMR, UV-Vis absorption and luminescent spectroscopy. It was found, that each lanthanide ion of the [Ln(L)4]- complex anion is bonded to two oxygen atoms belonging to the phosphoryl and carboxyl groups of four bidentate chelated ligands, completing coordination number of lanthanide ion to eight. Analysis of signals integral intensity in the investigated NMR spectra of coordination compounds PPh4[LnL4] (Ln = La, Y) indicates the molar ratio of dimethyl-N-trichloroacetylamidophosphate ligand and tetraphenylphosphonium cation as 4:1, which corresponds to the proposed structure of the complexes. According to the absorption spectroscopy investigations data there is one type of lanthanide sites in the complexes. Low symmetry of lanthanide ion coordination environment was concluded from bands ratio in the europium complex luminescence spectrum. From the TGA analysis the stability of the coordination compounds till 160°C can be concluded. It was shown that tetraphenylphosphonium cation sensitizes europium ion emission and photo-excitation of PPh4[EuL4] complex by UV light results in red Eu3+ centered luminescence with dominating band of 5D0‑7F2 transition in the spectrum and decay time equal one and a half millisecond
Keywords: carbacylamidophosphates, rare earth metals, coordination compounds, lanthanide luminescence